Competence and Competence Frameworks in Career Guidance: Complex and Contested Concepts - Sultana, Ronald G. (International Journal for Educational and Vocational Guidance, 2009)
This paper considers some of the debates surrounding the term competence and the relevance that these have for the development of competence frameworks. Such frameworks are increasingly on the agenda, since they purport to support training programme development, to identify competence gaps, to promote self-development, and to ensure common standards. This paper shows, however, that notions of competence have specific meanings in particular contexts, that they have been contested, and that they have fallen into and out of favour over time. The paper concludes by teasing out the implications that competing definitions of competence have for the guidance field.
Keywords: compétence; orientation